Problemy finansowania infrastruktury w gminach województwa poznańskiego w warunkach gospodarki rynkowej - Chabierska, Ewa; Noweta, Dariusz (Wydział Prawa i Administracji UAM, 1992)
The questionnaire research carried out by the authors were to provide the answer to the following question: "who, and to what degree, participates in costs of financing infrastructural investment in Poznan region villages?". The authors have included into their research the sources of financing of the following infrastructural elements: bank networks, including PKO outlets, village roads, dumping grounds, sewage and telephone networks. Much stress has been put on analyzing agricultural crediting system. Critical remarks of farmers on interest rates and changes in interest rates influencing the profitability of agricultural production, as well as on the circulation of documents in banks and the coiTelation between the repayment period and the production cycle are very important from a practical point of view. The research shows that in most cases the investment is financed by communal budgets, with little participation on the part of inhabitants in the form of labour and equally little participation on the part of other economic units, such as State Farms and Agricultural Cooperatives. However, the income of communes is diversified and may turn out to be insufficient for financing the investment. It may hinder the prospective development of infrastructure. It seems that a complex and rational development of infrastructure may be achieved only if communal budgets and the State budget were jointly engaged in a central and regional program of infrastructural investment.
Problems of financing infrastructure in Poznań region communes in conditions of market economy